PREVALENCE AND ANTIBIOTIC SUSCEPTIBILITY PATTERN OF PSEUDOMONAS SPECIES ISOLATED FROM CLINICAL SAMPLES IN A TERTIARY CARE HOSPITAL - RAHMAN, M. ABDUR; NAIR, POOJA (International Journal of Current Pharmaceutical Research, 2021)
Objective: Pseudomonas aeruginosa is the commonest agent causing opportunistic nosocomial infections, contributing to mortality and morbidity worldwide. Along with its intrinsic and acquired resistance mechanisms, infections caused by Pseudomonas species further lead to treatment failure. This study was done to determine the prevalence and antimicrobial susceptibility pattern of different species of Pseudomonas isolated from various clinical samples by phenotypic methods. Methods: This study involved the examination of clinical samples for various species of Pseudomonas by using different standard biochemical tests. Their antimicrobial susceptibility profile was performed by the Kirby Bauer disc diffusion method. Analysis of the antibiogram pattern was done to study the multi-drug resistance among Pseudomonas species. Results: Out of the 1249 bacterial isolates, Pseudomonas species accounted for 12.9%. Pseudomonas species showed maximum resistance to gentamicin (31.4%), followed by ciprofloxacin (30.2%. and showed the least resistance tocolistin and polymyxin B. 46 isolates out of the 162 (28%) were found to be Multi-Drug Resistant (MDR) Pseudomonas aeruginosa. Conclusion: The present study highlights that Pseudomonas species remains a major cause of hospital-acquired infections. Multidrug resistance was observed in most of the strains, which makes the therapeutic options more difficult. Surveillance of antimicrobial resistance and strict infection control measures are essentially to be practiced in managing and control of infections caused by Pseudomonas.